KONSTRIBUSI KEBANGSAAN KIAI HASYIM ASY’ARI: Membangun Relasi Harmonis Islam dan Indonesia - Sholikah Sholikah; Nurotun Mumtahanah (Universitas Islam Lamongan, 2021)
Thinking about kalam is very important for all, especially academics. Aside from beig historical data, it can also be used as a source of knowledge, so it can be applied to current and future lives. One of the kalam thinkers in Indonesia is KH. Hasyim Asy’ari. This research is done by a qualitative approach, the source of information obtained from the library (library research). The autor faund that Hadratusy Syaikh Hasyim Asy’ari is a charismatic people and nation,s best son. His thinking about kalam was influenced socio-historical conditions when he lived. Among these are various reform teachings from reformers for the Indonesian Muslim Community, in addition to the presence of the invaders. From these conditions he established the pesantern and NU organizations. Together with the to organizations, kiai Hasyim issued a fatwa on jihad and the elimination of seven controversial word in the Piagam Jakarta.